Challenges in pulmonary fibrosis · 1: Use of high resolution CT scanning of the lung for the evaluation of patients with idiopathic interstitial pneumonias - Gotway, Michael B (BMJ Group, 2007)
High resolution CT (HRCT) scanning has contributed significantly to the evaluation of patients with interstitial lung disease and is particularly useful in the diagnosis of idiopathic pulmonary fibrosis (IPF). The characteristic radiographic features of the idiopathic interstitial pneumonias on HRCT scans have been increasingly analysed and are now fairly well described. Based on current data, HRCT scanning can provide a confident, highly specific diagnosis of IPF in many patients with diffuse lung disease. This article reviews an organised approach to HRCT scanning and identifies the features that allow an accurate diagnosis of the idiopathic interstitial pneumonias to be made. The role of surgical lung biopsy is discussed in the diagnosis of cases when a definite HRCT diagnosis cannot be made.